2022
DOI: 10.1183/13993003.01390-2022
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of coadministration of COVID-19 and influenza vaccination

Abstract: Seasonal influenza vaccination is established as important infection prevention measure, especially among highly exposed healthcare workers (HCWs) [1]. Coadministration with the third dose of COVID-19 vaccine could be an efficient strategy protecting HCWs from two major viral respiratory infections [2][3][4]. To date, the humoral immunogenicity and side-effects of a coadministered third COVID-19 and a seasonal quadrivalent influenza vaccine are still unclear, and the available data is limited in transferabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Of the 3 study groups, those who received SIV alone experienced the least reactogenicity, while COVID-19 vaccination alone elicited similar reactogenicity to that of the coadministration of COVID-19 vaccine with SIV. These findings are similar to those of trials that investigated the coadministration of SIV and COVID-19 vaccines and found that coadministration of both vaccine groups was similar to COVID-19 vaccination alone in terms of adverse reactions …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Of the 3 study groups, those who received SIV alone experienced the least reactogenicity, while COVID-19 vaccination alone elicited similar reactogenicity to that of the coadministration of COVID-19 vaccine with SIV. These findings are similar to those of trials that investigated the coadministration of SIV and COVID-19 vaccines and found that coadministration of both vaccine groups was similar to COVID-19 vaccination alone in terms of adverse reactions …”
Section: Discussionsupporting
confidence: 85%
“…These findings are similar to those of trials that investigated the coadministration of SIV and COVID-19 vaccines and found that coadministration of both vaccine groups was similar to COVID-19 vaccination alone in terms of adverse reactions. 4,5,[7][8][9] When assessing immunogenicity, we estimated a mild decrease in anti-spike IgG titers, with a point estimate of 16%, and a confidence interval not greater than 31%. Findings from previous immunogenicity and correlates of protection studies suggest that changes in IgG titers to such an extent did not greatly impact vaccine effectiveness, 13 vaccine effectiveness against substantially symptomatic disease, 14 or a SARS-CoV-2 diagnosis risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this also means that our main estimates primarily reflect the co-administration with the seasonal influenza vaccine. This is reassuring, since coadministration has been speculated to blunt the immune response, [14][15][16][17][18][19] and if that is the case, our estimates are likely conservative.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 89%
“…Study participants administered with a different COVID-19 vaccine as second booster were excluded. As coadministration of COVID-19 and influenza vaccination might influence immunogenicity and side effects,( 4 ) individuals receiving a simultaneous influenza vaccination were also excluded.…”
mentioning
confidence: 99%